Significant association between thyroid hormones and erythrocyte indices in euthyroid subjects - Bremner, A.; Feddema, P.; Joske, D.; Leedman, P.; O'Leary, Peter; Olynyk, John; Walsh, J. (Blackwell Publishing Ltd, 2012)
Objective: Hypothyroidism and hyperthyroidism are each associated with anaemia, but relationships between thyroid function and erythrocyte indices in euthyroid subjects have not been examined. The aim of this study was to examine these relationships in a community-based cohort. Design, subjects and measurements: Linear regression models with free T4, free T3 and TSH as predictors of erythrocyte indices and serum iron parameters were fitted to data from a cohort of 1179 participants in the 1994 Busselton health study and a subset of 1011 euthyroid participants. All models were adjusted for age, age2, sex and an age–sex interaction. Results: In the full cohort and euthyroid subset, there were significant, positive linear relationships between free T4 and each of haemoglobin, haematocrit and erythrocyte count (P < 0•01 for each), such that in euthyroid participants, each 1•0 pm increase in free T4 was associated with an increase in haemoglobin of 0•39 g/l. There were significant relationships between free T3 and each of haemoglobin, haematocrit and erythrocyte count (P < 0•001 for each), with the best model fits obtained using free T32, indicating curved relationships. TSH had a significant (P < 0•05) inverse relationship with serum iron and transferrin saturation in the full cohort and the euthyroid subset. Serum iron concentrations were lower in participants with subclinical hypothyroidism (n = 87) than euthyroid subjects [mean (SD) 15•9 (4•7) vs 18•4 (6•0) μm, P = 0•001]. Conclusion: In euthyroid subjects, small differences in thyroid function are associated with significant differences in erythrocyte indices.